Bacillus atrophaeus MFDV2 RHIZOBACTERIA ISOLATE INCREASES VEGETATIVE GROWTH, YIELD, AND FRUIT SIZE OF BANANA PLANT - Lütfi Pırlak; Yaşar Akbaş; Mesude Figen Dönmez (Indonesian Journal of Agricultural Science, 2019)
Plant growth-promoting rhizobacteria have important roles in soil fertility and have been manipulated for ecologically friendly crop production. The study aimed to determine the effects of a biological agent (Bacillus atrophaeus MFDV2) on the growth, yield, and quality of the banana plant. The study was conducted in 2017–2018 using the banana Dwarf Cavendish clone. Bacterial isolate was cultured on nutrient agar and stored at 30 °C for 24 hours. The culture was then suspended in 0.1 M phosphate buffer to 109 CFU ml-1. The bacterial suspension was applied as foliar, soil and foliar + soil once every two months starting from February. One liter of suspension was applied on the soil and over the leaves per plant. The results showed that the effect of bacterial treatment did not increase stem circumference and leaf length, but it was a significant increase in plant height, leaf number, and leaf width. The effects of bacterial application on banana bunch weight and fruit growth were statistically significant. All applications significantly increased the weight, with the highest increase occurring in foliar finger + soil application. While the effects on the finger diameter were statistically similar. Application on leaf + root has been the biggest increase in finger length. The effects of bacterial applications increased N, P, and K contents in the leaves. The study concluded that the application of Bacillus atrophaeus MFDV2 increased the vegetative growth and fruit quality of the banana plant, so it is advisable to be used in organic banana farming.